Conceptual and Practical Concerns for the Effectiveness of the Right to Housing - Nico Moons; Bernard Hubeau (Oñati Socio-Legal Series)
Anno 2014, it is rather an exception to the rule that a state does not have a set of fundamental social rights incorporated into its constitution. Unfortunately however, this does not mean by far that social rights have consistently been given the same kind of treatment as other constitutional rights. A large discrepancy between the wide recognition of these rights in theory on the one hand and its influence in practice on particularly the more disadvantaged people in society is still very noticeable. The apparent failure to adequately implement fundamental social rights and their limited practical impact raise questions regarding their effectiveness. Evidently, the same applies with specific regard to the right to housing. Here, the question has been raised whether the right to housing ought to be approached as a so called obligation of result. To what extent might such a modification enhance the practical significance of such a right?